Implementation of Qaulan Karima Principles of the Coaches in Improving the Speaking Ethics of Mosque Youth Al-Falah Bantan Village, Medan Tembung, Medan City - Ahmad Andrehadi Hasibuan; Rubino Rubino (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the implementation of the principle of Qaulan Karima Pembina as a strategy in improving the speaking ethics of adolescents in Al-Falah Mosque. The research method used is a qualitative approach. Data was collected through observation, in-depth interviews with youth members of the al-Falah mosque, and document analysis. The results of the study show that the implementation of the Qaulan Karimah Pembina instructor at the Al-Falah Mosque has been quite effective and has also made a significant contribution in forming positive character and increasing the morality of adolescents. The coaching is carried out through a series of implementations based on previous research references that also support the formation of adolescent speaking ethics. The implications of this study are the importance of the active role of mosques in the moral and spiritual development of the younger generation, as well as the need for support from various parties to ensure the sustainability and effectiveness of the coaching program.